الكفاءة الانتاجية الداخلية الكمية في كليات الطب – جامعة بغداد (بحث مستل عن رسالة الماجستير الموسومة ) (Journal Of Educational and Psychological Researches, 2015)
The research aims at the following:- Identifying the level of internal quantity efficiency in Medical colleges, University of Baghdad by determining the level of productivity for one group for the total batch according to sex variable (males and females). Procedures of the studyThe researcher used the descriptive and analytical method has been used by following them up enhanced by flow indicators of students for one session  depending on   special statistical data  analyss .The results are as follows: - The Faculty of Medicine were higher productivity scholarships for one year and two years of schooling, as well as the highest in the efficiency of the Faculty of Dentistry and the Faculty of Medicine of Canada, which was the weakest in the productivity and efficiency coefficient. At the level of sex male / female ratio of the productivity of study for one year at the Faculty of Medicine at the female cohort were higher than those of the male regiment. In the Faculty of Medicine of Canada was the productivity of female scholarship for one year rate three times higher than the proportion of male productivity. In the Faculty of Dentistry, the productivity ratio study for one year in female regiment higher than twice the productivity of male and female two years of schooling were higher productivity than the males. The females efficiency coefficient higher than males efficiency coefficient.